Digital initiative a pilot project of Buddhist Manuscripts of Arunachal Pradesh, India - Motebennur, Maltesh Ningappa (Qualitative and Quantitative Methods in Libraries; Vol 7 No 2 (2018): June 2018 Issue, 2019)
The North East India is the meeting ground of various cultures since pre historic period. Before independence, it consisted of independent Kingdom of Assam, Manipur, Tripura and some hill regions. In the present scenario, it is estimated that only in Tawang monastery there are more than five thousand rare Buddhist manuscripts that contains knowledge on religion, philosophy, medicine, Lord Buddha’s original preaching’s etc. Such rare manuscripts were surveyed and pilot project has been taken to initiate to digitize these manuscripts and preserve for the future generation.